Propaganda Partai Hijau dalam Perspektif Green Politics Terhadap Dampak Perubahan Iklim di Australia - Nicholas Filiata Damay Setiawan; Setyasih Harini; Untari Narulita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The background of this research focuses on the impact of climate change in Australia, caused by extreme temperature fluctuations that have resulted in various social, environmental, and economic consequences. This study is analyzed using Green Politics theory and Propaganda theory, both of which play a significant role in shaping policies and public perceptions related to these issues. The research method used is a descriptive qualitative approach, which guides the investigation to explore or capture the situation to be studied comprehensively, broadly, and in depth, specifically through the analysis of Green Party propaganda from the perspective of Green Politics concerning the impact of climate change in Australia. Data were collected through public documents, books, scientific journals, mass media, and websites accessed from the internet. The findings indicate that Green Politics theory provides an effective framework for understanding how environmental policies in Australia can be influenced by political ideologies and economic interests. Meanwhile, propaganda theory reveals that the propaganda techniques used by the Australian Green Party, as proposed by Harold Lasswell, have proven to significantly increase public awareness and support for more progressive climate policies, despite facing inherent challenges. This study concludes that the integration of these two theories offers deep insights into the political dynamics underlying responses to climate change in Australia.